Early Liver Transplantation for Severe Alcohol-Associated Hepatitis and a History of Prior Liver Decompensation. (11th December 2022) - Weinberg, Ethan M.; Dukewich, Matthew; Jakhete, Neha; Stonesifer, Elizabeth; Im, Gene Y.; Lucey, Michael R.; Shetty, Kirti; Rice, John P.; Victor, David W.; Ghobrial, Mark R.; Shetty, Akshay; Rutledge, Stephanie M.; et al.
Abstract : INTRODUCTION: In the published studies of early liver transplantation (LT) for alcohol-associated hepatitis (AH), patients with a prior liver decompensation are excluded. The appropriateness of this criteria is unknown. Methods: Among 6 American Consortium of Early Liver Transplantation for Alcohol-Associated Hepatitis sites, we included consecutive early LT for clinically diagnosed AH between 2007 and 2020. Patients were stratified as first vs prior history of liver decompensation, with the latter defined as a diagnosis of ascites, hepatic encephalopathy, variceal bleeding, or jaundice, and evidence of alcohol use after this event. Adjusted Cox regression assessed the association of first (vs prior) decompensation with post-LT mortality and harmful (i.e., any binge and/or frequent) alcohol use. Results: A total of 241 LT recipients (210 first vs 31 prior decompensation) were included: median age 43 vs 38 years ( P = 0.23), Model for End-Stage Liver Disease Sodium score of 39 vs 39 ( P = 0.98), and follow-up after LT 2.3 vs 1.7 years ( P = 0.08). Unadjusted 1- and 3-year survival among first vs prior decompensation was 93% (95% confidence interval [CI] 89%–96%) vs 86% (95% CI 66%–94%) and 85% (95% CI 79%–90%) vs 78% (95% CI 57%–89%). Prior (vs first) decompensation was associated with higher adjusted post-LT mortality (adjusted hazard ratio 2.72, 95% CI 1.61–4.59) and harmful alcohol use (adjusted hazard ratio 1.77, 95% CI 1.07–2.94). DISCUSSION: Prior liver decompensation was associated with higher risk of post-LT mortality and harmful alcohol use. These results are a preliminary safety signal and validate first decompensation as a criterion for consideration in early LT for AH patients. However, the high 3-year survival suggests a survival benefit for early LT and the need for larger studies to refine this criterion. These results suggest that prior liver decompensation is a risk factor, but not an absolute contraindication to early LT.